Exploring teacher leadership readiness in compulsory schools and the contributing two factors in China context: the mediating role of teacher leaders - Deng, Fengchi; Leksansern, Arisara (Kasetsart Journal of Social Sciences, 2026)
The objectives of this mix-methods study were: (1) to define the existing levels of teacher leadership readiness of compulsory schools; (2) to examine the role of teacher leaders as a mediator between contributing factors and teacher leadership readiness, and (3) to propose guideline for improving teacher leadership readiness. Data were collected via questionnaires from 362 teachers and semi-structured interviews with six backbone teachers. The quantitative part was focused on descriptive statistics (frequency, percentage, mean, standard deviation) and the inferential statistics (t-test, ANOVA, correlation analysis, regression analysis, path analysis) while the qualitative part was in content analysis. Findings showed imbalanced teacher leadership readiness, significant gender differences, and teacher leaders as partial mediators for the two key contributing factors: teachers’ characteristics, colleagues’ relationships. The interviews outlined that (1) teacher leaders are recognized as leadership roles in position-based as well as in activities-based occasions, and (2) offering sufficient supply positions and opportunities is the prominent facilitating motivation yet the dominant inhibitor is time limit and extra workload for leadership roles. Rooted in the findings from these two sections, the study provided a guideline for teachers to execute effective teacher leadership practices, principals to take advantages of the mediating role of teacher leaders and policy makers to resources allocation.